Global Income Inequality : What It Is and Why it Matters - Milanovic, Branko (World Bank, Washington, DC, 2012)
The paper presents a nontechnical summary of the current state of debate on the measurement and implications of global inequality (inequality between citizens of the world). It discusses the relationship between globalization and global inequality. And it shows why global inequality matters and proposes a scheme for global redistribution.